Odpowiedzi

2009-12-25T21:10:08+01:00
(3x-1)²+(3x-1)(3x+1)=9x²-6x+1+ 9x²-1=18x²-6x
18x²-6x=18* (½)² -6*(½)=4,5-3=1,5
2009-12-25T21:33:02+01:00
(3x-1)²+(3x-1)(3x+1) dla x=½

9x² - 6x + 1 + 9x² - 1 = 9*1/4 - 6*1/2 + 1 + 9*1/4 - 1 = 9/4 - 3 + 9/4 = 18/4 -3 = 4,5 - 3 = 1,5
Najlepsza Odpowiedź!
2009-12-25T22:20:34+01:00
(3x-1)²+(3x-1)(3x+1) dla x=½

najpierw wymnażamy:
(3x-1)²+(3x-1)(3x+1)=
9x²+1-6x+9x²+3x-3x-1=
18x²-6x

podstawiamy pod x wartość ¹/₂

18•(¹/₂ )²- 6•¹/₂ =
18•¹/₄ - 3
¹⁸/₄- 3=
4,5- 3= 1,5

wartość dla x= ¹/₂ jest równa 1,5